Machine Translation in Translation Education: Pedagogical Potential, Cultural Limits, and Critical Practice - Tirza Annette Kumayas; Maniku Jein; Jeihn Novita Christanty Budiman; Fergina Lengkoan; Imelda Seska Lolowang; Vidi Ferdinand Wenas Sampow (PT. Global Research Collaboration, 2026)
The growing integration of machine translation (MT) in higher education translation courses raises important questions about cultural nuance, pedagogical design, and student competence development. This qualitative case study examines how students and lecturers in a Translation and Interpreting course at a university in Manado, North Sulawesi, Indonesia, perceive and engage with MT tools in their learning and teaching. Data were generated through semi-structured interviews with fourteen students and two lecturers, documentary analysis of translation assignments comparing raw MT output with post-edited final versions, and classroom reflections. Thematic analysis revealed three interconnected patterns: MT functions productively as a pedagogical scaffold when embedded in structured comparison and post-editing tasks; MT consistently fails to handle culturally embedded language, including idioms, humor, and pragmatic markers of address; and students demonstrate meaningful shifts toward critical MT use following sustained instructional engagement, though dependency risks persist. These findings indicate that MT should be positioned as a tool for developing evaluative literacy rather than a substitute for translator competence, and that effective integration requires explicit pedagogical guidance and institution-level policy frameworks.